Design and analysis of a slider-level piezoelectric sensor array for head-disk contact detection - Yuan, Yanhui (2013)
To realize higher areal densities towards 10 Tbit/in2, the ever decreasing flying height of the slider approaches the near-contact regime. It is essential to monitor head-disk interactions to prevent instability and damage to the head-disk interface. In this study, a piezoelectric sensor array embedded on the slider was proposed for head-disk contact detection. Integrability of the sensor array with standard slider fabrication process was considered in the design. Dynamic response of the sensor array to typical contact scenarios was obtained by finite element analysis. Simulation results suggest that the sensor array is adequately sensitive and capable of identifying contact location under intermittent head-disk contact.